Relationship between physical activity level and BMI among Pakistani laborers in Saudi Arabia: a cross-sectional study - Kashif , Seemin; Ahmad, Hajra; Kashif Malik , Muhammad; Zaheer Ahmed (Journal of the Pakistan Medical Association, 2022)
Abstract Objectives: To study the level of physical activity of Pakistani labourers in Saudi Arabia, and to find its relationship with body mass index. Method: The observational study was conducted inside the Pakistan Embassy in Riyadh, Saudi Arabia, from October 2017 to March 2018, and comprised Pakistani males aged 22-60 years doing unskilled and semi-skilled jobs. Body mass index was calculated, and the level of physical activity was assessed using the short form International Physical Activity Questionnaire. Data was analysed using SPSS 20. Results: There were 130 subjects with mean age of 33.53±7.9 years. There were 109(83.8%) subjects aged <40 years, and 21(16.2%) were aged 40 years. Mean body mass index of the sample was 26.13±5.29kg/m². Overall, 71(54.6%) participants were insufficiently active having energy expenditure <600 metabolic equivalent of task in minutes per week. No statistically significant result was found when total energy expenditure was considered (p0.05), but significant result was found for energy expenditure due to ‘walk alone’ (p0.05). Significant correlation was found between profession and overall energy expenditure and job-related energy expenditure. Significant but weak positive correlation was found between body mass index and walk-related energy expenditure (r=0.279, p0.001). Conclusion: Mean body mass index of the sample was high compared to South Asian cut-off values, and the level physical activity was very low, but the findings failed to show an inverse relationship between physical activity level and body mass index. Key Words: Relationship, Physical activity level, BMI, Pakistani labourers, Saudi Arabia, Cross-sectional.